2010
DOI: 10.1086/648530
|View full text |Cite
|
Sign up to set email alerts
|

Wealth Transmission and Inequality among Hunter‐Gatherers

Abstract: We report quantitative estimates of intergenerational transmission and population-wide inequality for wealth measures in a set of hunter-gatherer populations. Wealth is defined broadly as factors that contribute to individual or household well-being, ranging from embodied forms such as weight and hunting success to material forms such household goods, as well as relational wealth in exchange partners. Intergenerational wealth transmission is low to moderate in these populations, but is still expected to have m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 56 publications
(51 reference statements)
4
91
2
4
Order By: Relevance
“…In the study of hunter -gatherer inter-generational resource transfers, Smith et al [19] concluded, unsurprisingly, that material wealth was much less important as a transmitted resource than embodied or relational wealth, but still found that values of the intergenerational wealth transmission coefficient were such that the offspring of an individual in the top 10 per cent of the population would be at least three times more likely to be in that top 10 per cent than the offspring of an individual from the bottom 10 per cent. Moreover, degrees of inequality in these societies were not insignificant, coming out close to those for present-day industrial Denmark, based on the value of the Gini coefficient (a measure of inequality generally based on the income distribution of a society that ranges between 0, for complete equality, when everyone has the same share of the total income, and 1, for complete inequality, corresponding to a situation in which one member of the society monopolizes all the income and the rest have nothing).…”
Section: Inter-generational Resource Transfersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of hunter -gatherer inter-generational resource transfers, Smith et al [19] concluded, unsurprisingly, that material wealth was much less important as a transmitted resource than embodied or relational wealth, but still found that values of the intergenerational wealth transmission coefficient were such that the offspring of an individual in the top 10 per cent of the population would be at least three times more likely to be in that top 10 per cent than the offspring of an individual from the bottom 10 per cent. Moreover, degrees of inequality in these societies were not insignificant, coming out close to those for present-day industrial Denmark, based on the value of the Gini coefficient (a measure of inequality generally based on the income distribution of a society that ranges between 0, for complete equality, when everyone has the same share of the total income, and 1, for complete inequality, corresponding to a situation in which one member of the society monopolizes all the income and the rest have nothing).…”
Section: Inter-generational Resource Transfersmentioning
confidence: 99%
“…Such intensification is generally associated with increasing sedentism, both appearing at the end of the last Ice Age, most probably in connection with increasing population [31] and greater climatic stability [32]. As the authors note, Smith et al's analyses [19] described above did not include any of this type of hunter-gatherer society because none are still extant.…”
Section: Inter-generational Resource Transfersmentioning
confidence: 99%
“…Table 2 reflects our impressions from "Wealth" that emphasized the importance of relational capital for cultural success, even (or especially) among egalitarian horticulturalists, and the lower importance of material capital. Only hunter-gatherers show a higher mean a for relational capital and a lower a for material capital (see Smith et al 2010). Figure 1 illustrates the a's for all horticultural populations in a ternary plot.…”
Section: Alphas (A's) From Production Functionmentioning
confidence: 99%
“…Estratos sociais são condições inerentes à existência de desigualdade, dado que alguns grupos possuem mais (poder, riqueza material), enquanto outras categorias, classes ou grupos, menos (FLANNERY, 1972;KAPLAN et al, 2009;SUMMERS, 2005 GURVEN et al, 2010;MULDERT et al, 2010;SHENK et al, 2010;SMITH et al, 2010a;SMITH et al, 2010b), conforme será explicitado neste capítulo, quando definirmos as diferenças entre os grupos igualitários e as chamadas sociedades desiguais.…”
Section: O Que Não Foi Abordado E Porqueunclassified
“…Complementarmente, em termos sociais, notou-se que o processo de transformação das populações anteriormente igualitárias teria envolvido o crescimento populacional -fenômeno presente em ambos os estudos de caso -a partir de pequenos grupos compostos de algumas dezenas de indivíduos (ANDREFSKY, 2004;WILKINSON, 1990) Entretanto, as dinâmicas de fluxo de recursos dentro da população, o compartilhamento e a troca (BOWLES, SMITH;MULDER, 2010;GURVEN et al, 2010;MULDER et al, 2010;SHENK et al, 2010;SMITH et al, 2010a;SMITH et al, 2010b), assim como as relações de distribuição, competição e cooperação (CLARK; BLAKE, 1994;FRANGIPANE, 2007;HAYDEN, 1981;KAPLAN et al, 2009;KENNETT et al, 2008) nos pareceram plausíveis entre as populações materialmente igualitárias (Arnold, 2004, Sahlins 1972 Dadas as condições de inicialização do modelo, a dinâmica entre os indivíduos se dá através de sucessivas iterações ao longo do tempo, as quais seguem, todas, um mesmo caminho geral (Figura 5.1). Cada unidade temporal -dada a composição discreta do tempo -representa um passo (step) na realização da dinâmica, composta por duas mil unidades.…”
Section: Detailsunclassified